2000
DOI: 10.1074/jbc.275.9.6509
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylglycerol Is Involved in the Dimerization of Photosystem II

Abstract: Photosystem II core dimers (450 kDa) and monomers (230 kDa) consisting of CP47, CP43, the D1 and D2 proteins, the extrinsic 33-kDa subunit, and the low molecular weight polypeptides PsbE, PsbF, PsbH, PsbI, PsbK, PsbL, PsbTc, and PsbW were isolated by sucrose density gradient centrifugation. The photosystem II core dimers were treated with phospholipase A2 (PL-A2), which cuts phosphatidylglycerol (PG) and phosphatidylcholine molecules at the sn-2 position. The PL-A2-treated dimers dissociated into two core mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(102 citation statements)
references
References 48 publications
10
92
0
Order By: Relevance
“…In addition to these 22 helices we have identi¢ed at least ten further transmembrane helices in the PS II core complex ; B. Hankamer, E. P. Morris and J. Barber, unpublished data). One of these helices belongs to PsbH and, although not yet con¢rmed, we believe this protein to be located at the interface between the two monomers within the dimer where it may play a role in stabilizing the dimeric con¢guration by interacting in its phosphorylated or non-phosphorylated state with the thylakoid lipid phosphatidylglycerol which has the usual transhexadecanoic fatty acid (Kruse et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these 22 helices we have identi¢ed at least ten further transmembrane helices in the PS II core complex ; B. Hankamer, E. P. Morris and J. Barber, unpublished data). One of these helices belongs to PsbH and, although not yet con¢rmed, we believe this protein to be located at the interface between the two monomers within the dimer where it may play a role in stabilizing the dimeric con¢guration by interacting in its phosphorylated or non-phosphorylated state with the thylakoid lipid phosphatidylglycerol which has the usual transhexadecanoic fatty acid (Kruse et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…PG plays an important role in the oligomerization of the light harvesting complex and the dimerization of PSII (McCourt et al, 1985;Krupa et al, 1987;Kruse et al, 2000). It is also required for both the electron-acceptor side and the donor side of PSII (Sakurai et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly one protein in this complex called intrinsic D1 core peptide has high binding affinity for PG which promotes dimerization of the complex. Thin layer chromatography analysis showed that photosystem II dimers contained four times more PG than their monomeric counterparts but with similar levels of phosphatidylcholine (49). PG depletion from thylakoid membrane in PG mutants causes dissociation of extrinsic proteins and PSII dysfunction (50).…”
Section: Pg In Photosynthesis and Electron Chain Transportmentioning
confidence: 99%